1996
DOI: 10.1074/jbc.271.9.4653
|View full text |Cite
|
Sign up to set email alerts
|

The Selenoenzyme Phospholipid Hydroperoxide Glutathione Peroxidase Controls the Activity of the 15-Lipoxygenase with Complex Substrates and Preserves the Specificity of the Oxygenation Products

Abstract: Mammalian 15-lipoxygenases have been suggested to be involved in cell differentiation and atherogenesis because of their capability of oxygenating polyenoic fatty acids esterified to biomembranes and lipoproteins. We investigated the interaction of the lipid-peroxidizing 15-lipoxygenase and the hydroperoxy lipid-reducing phospholipid hydroperoxide glutathione peroxidase during their reaction with biomembranes and lipoproteins and obtained the following results. 1) Lipoxygenase treatment of submitochondrial mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(31 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…This is based on knowledge that these enzymes require a low level of pre-existing PLOOH or ChOOH (a peroxide tone) for optimal activity and that GPx4 can negatively affect this. In support of this, it was found, for example, that (i) 5-LOX expression/activity was strongly upregulated in GPx4-deficient (Se-starved) cells, and (ii) 15-LOX-induced lipid peroxidation in membranes and LDL was significantly suppressed by GSH/GPx4 [31,32]. …”
Section: Two-electron Reduction Of Lipid Hydroperoxidesmentioning
confidence: 95%
“…This is based on knowledge that these enzymes require a low level of pre-existing PLOOH or ChOOH (a peroxide tone) for optimal activity and that GPx4 can negatively affect this. In support of this, it was found, for example, that (i) 5-LOX expression/activity was strongly upregulated in GPx4-deficient (Se-starved) cells, and (ii) 15-LOX-induced lipid peroxidation in membranes and LDL was significantly suppressed by GSH/GPx4 [31,32]. …”
Section: Two-electron Reduction Of Lipid Hydroperoxidesmentioning
confidence: 95%
“…The proposed mechanism was the antioxidant capabilities of GPx4 and the ability to reduce FAHP to hydroxyl derivatives. Others found that GPx4 reduced 15-HPETE to 15-HETE and pre-incubation of endothelial cells with GPx4 could prevent peroxide formation ( 72 ) . Both TrxR and Sepp1 also were shown to have lipid hydryperoxidase activity for 15-HPETE, thus supporting the contention that these selenoproteins can function as antioxidant enzymes against highly reactive hydroperoxy intermediates formed during eicosanoid metabolism ( 35 , 37 ) .…”
Section: Can Selemium and Selenoproteins Have An Impact On Inflammatimentioning
confidence: 99%
“…1,2 The nomenclature of the LOX isozymes is loosely based on the carbon position (e.g., 5, 12, or 15) at which they oxidize arachidonic acid to form the corresponding hydroperoxyeicosatetraenoic acid (HpETE), 3 which is reduced to the hydroxyeicosatetraenoic acid (HETE) by intracellular glutathione peroxidases. 4 Human lipoxygenases and their metabolites have been implicated in numerous diseases. 5-LOX has been implicated in cancer, 5 asthma, 6,7 COPD, 8 allergic rhinitis, 9 osteoarthritis, 10,11 and atherosclerosis, 1214 whereas platelet-type 12-LOX has been implicated in diabetes, 15,16 blood coagulation, 17 psoriasis, 18 and cancer.…”
Section: Introductionmentioning
confidence: 99%